Synthesis and Potential Applications of Modified Xanthan Gum - Abu Elella, Mahmoud H. (Journal of Chemical Engineering Research Updates, 2021)
Designing high-performance adsorbents for wastewater treatment and antibacterial materials for food and biomedical applications and excellent drug carrier to prolong time retention of the therapeutic drug based on biodegradable polymers has gained more interest in recent years. Among these materials, xanthan gum, which is a natural polysaccharide and plays a vital role in various applications such as industry, enhanced oil recovery, water-based paints, pharmaceuticals, and personal care products because it has excellent properties such as biodegradability and non-toxicity. On the other hand, it has many affected limitations, including microbially attack, poor thermal and mechanical stability, and low surface area. So, in this review, we focused on the advanced modifications on xanthan gum and their applications in wastewater treatment, protein delivery, and designing antimicrobial materials.